Economic Growth, Technological Progress, and Social Capital: The Inverted U Hypothesis - Angelo Antoci; Fabio Sabatini; Mauro Sodini (Economics and Econometrics Research Institute (EERI), 2011)
We set up a theoretical framework to analyze the possible role of economic growth and technological progress in the erosion of social capital. Under certain parameters, the relationship between technological progress and social capital can take the shape of an inverted U curve. We show the circumstances allowing the economy to follow trajectories where the stock of social capital grows endogenously and unboundedly.
Keywords: O33; Z13; 330; Economic growth; social capital; social norms; technological progress